Efetividade do direito e as respostas penais no estado democrático de direito brasileiro - Teixeira, Mônica Regina (2024)
The due process of law guarantees the right to adversarial proceedings and a fair trail, as well as prohibiting the application of cruel penalties, limiting the State´s right to punish. However, the evolution of society has demonstrated that the legal system of criminal justice has failed from crime prevention to the execution of the sentence. The present work aims to analyze the penalty itself and its effects when applied to the specific case as the only form of punishment and reestablishment of the offender to life in society, as well as the object of this study as the use of alternative penalties and encouragement of consensual justice practices. and restorative can contribute positively to the offender, the victim and society. One of the great challenges of this research was the collection of updated statistical data, since the information released by public bodies is not frequently updated. The data located support that it is not enough to work only on the issue of incarceration as the only means of resocializing the offender, we must act preventively so that he does not violate the law and positively in the post-infraction period with a view to resocialization. The present study was carried out using qualitative research methodology, through the analysis of fundamental historical questions about the punitive system and the purpose of penalties, as well as changes in normative instruments that recognized both the figure of the State as holder of the right to punish and as a guarantor of fundamental rights and guarantees. During the course of this work, it was verified that the Federal Constitution of 1988 brought a focus on the protection of human rights, mainly with Regard to the violation of these rights and efforts have bem ade to evolve through timid public policies, but it appears that still there is great resistance in the development and application of preventive and ressocializing measures